Re-positive Cases of Nucleic Acid Tests in Discharged Patients With COVID-19: A Follow-Up Study - Qiao, Xi-Min; Xu, Xiao-Feng; Zi, Hao; Liu, Guo-Xiong; Li, Bing-Hui; Du, Xiang; Tian, Zhi-Hai; Liu, Xiao-Ying; Luo, Li-Sha; Wang, Xiao (Frontiers in Medicine, 2020)
Background: The frequent emergence of the re-positive patients with COVID-19 is a potential threat worldwide. This study aimed to describe data from admission to follow-up for patients with COVID-19 and analyze the possible causes for re-positive nucleic acid tests to provide more scientific basis for reducing the numbers of re-positive patients after discharge. Methods: We retrospectively recorded 15 patients with COVID-19 admitted to the Xianyang Central Hospital, China. The baseline, exposure histories, clinical syndromes, laboratory characteristics, nucleic acid, and follow-up tests were analyzed, and the radiological characteristics of re-positive patient at different periods were compared. Results: Eight (53.33%) patients had the history of travel to Wuhan, four (26.67%) patients had close contact with confirmed patients, and one (6.67%) patient had close contact with suspected patients. After treatment, all patients had two consecutively negative nucleic acid tests and were discharged from hospital. All patients were followed up for more than 14 days, and the average time from discharge to the first follow-up was 14.67 ± 3.31 days (from 9 to 22 days). Most patients showed no clinical symptoms and negative nucleic acid tests, while one patient had an itchy throat, her CT scan showed a light density shadow in the right lower lobe of the lung, and the nucleic acid was once again positive. The second follow-up of the other 14 patients (except the re-positive one) was conducted 20.80 ± 7.78 days (from 13 to 30 days) after discharge, and all of them had negative nucleic acid tests. The positive patient was immediately readmitted and received a new round of treatment. Her family members and colleagues remained healthy until now. Conclusions: The quality of nucleic acid testing reagents should be enhanced, and the training of nucleic acid sampling operators should be strengthened to reduce the false-negative results in the nucleic acid of SARS-CoV-2; the clinical specimens of throat and nasopharynx swabs can be collected at the same time; IgM- and IgG-specific antibodies of SARS-CoV-2 should be carried out for discharged patients; the radiological characteristics should be evaluated strictly; and the discharge standard can be specified according to the baseline and severity of disease of patients.